2005
DOI: 10.1073/pnas.0507987102
|View full text |Cite
|
Sign up to set email alerts
|

Fcp1 directly recognizes the C-terminal domain (CTD) and interacts with a site on RNA polymerase II distinct from the CTD

Abstract: Fcp1 is an essential protein phosphatase that hydrolyzes phosphoserines within the C-terminal domain (CTD) of the largest subunit of RNA polymerase II (Pol II). Fcp1 plays a major role in the regulation of CTD phosphorylation and, hence, critically influences the function of Pol II throughout the transcription cycle. The basic understanding of Fcp1-CTD interaction has remained ambiguous because two different modes have been proposed: the ''dockingsite'' model versus the ''distributive'' mechanism. Here we demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 65 publications
(102 reference statements)
0
35
0
Order By: Relevance
“…In the S. pombe Fcp1 crystal structure (Ghosh et al 2008), the equivalent peptide makes extensive intramolecular hydrophobic contacts that would preclude its binding to TFIIF in the mode reported for a synthetic peptide derived from human Fcp1. Moreover, the relevance of TFIIF binding to S. pombe Fcp1 is unclear, because available evidence points to a direct interaction of SpFcp1 with Pol2 as a likely mode of SpFcp1 binding to the elongation complex (Kimura et al 2002;Suh et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In the S. pombe Fcp1 crystal structure (Ghosh et al 2008), the equivalent peptide makes extensive intramolecular hydrophobic contacts that would preclude its binding to TFIIF in the mode reported for a synthetic peptide derived from human Fcp1. Moreover, the relevance of TFIIF binding to S. pombe Fcp1 is unclear, because available evidence points to a direct interaction of SpFcp1 with Pol2 as a likely mode of SpFcp1 binding to the elongation complex (Kimura et al 2002;Suh et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Ccr4-Not complex was purified from yeast from a Caf40-or Not4-TAP strain containing a deletion of DST1 by tandem affinity purification (TAP) as described in a previous publication (13). RNAPII and its mutant derivatives were purified through Rpb4-TAP or Rpb8-TAP (for 4/7⌬ RNAPII) (18). The amount of RNAPII was estimated by Bradford assay using bovine serum albumin as a standard.…”
Section: Methodsmentioning
confidence: 99%
“…3A). Rbp1 is predominantly hypophosphorylated (Suh et al 2005; data not shown). All of the known core subunits of the Ccr4-Not complex were detected in the TAP purification, and its composition matched that published by others (Mulder et al 2007b;Azzouz et al 2009).…”
Section: Ccr4-not Directly Binds To Rnapii Elongation Complexesmentioning
confidence: 99%
“…TFIIS was expressed in Escherichia coli and purified as a histidinetagged protein (Kim et al 2007). Yeast RNAPII was purified as described in a previous study (Suh et al 2005). …”
Section: Coimmunoprecipitation and Protein Purificationmentioning
confidence: 99%
See 1 more Smart Citation